Polymorphisms in one-carbon metabolism pathway influence survival of gastric cancer patients received fluorouracil based adjuvant chemotherapy - Ting-Ting Zhao (临床与病理杂志, 2026)
Objective: We investigated the effects of polymorphisms of OCM associated genes and their interactions on the survival of GC patients receiving 5-FU-based regimens, including (MTHFR1298AC, 677CT), (MTRR66AG), (5′-UTR2R3R TS, 3′UTRins6del6) and (MTR 2756AG). Methods: A total of 297 chemotherapy patients and other 622 patients were recruited. The Cox regression analyses, logrank tests and Kaplan–Meier plots were adopted. Results: MTRR 66GA+GG and MTHFR1298CA+CC genotypes decreased death risk (HR =0.668, 95% CI, 0.470~0.949, HR =0.628, 95% CI, 0.422~0.935, respectively) but TS5′-UTR2R3R+2R2R genotypes increased death risk (HR =1.606, 95% CI, 1.121~2.301). The favorable prognosis improved when GC patients simultaneously had MTHFR1298 CA+CC and MTRR66GG+GA (HR =0.520, 95% CI, 0.285~0.947). Although MTHFR677TT+TC were not related with the prognosis of GC patients, the poorer prognosis obviously enhanced when patients simultaneously had TS5- UTR2R2R+2R3R and MTHFR677TT+TC (HR =2.152, 95% CI, 1.219~3.798). Conclusion: In all, polymorphisms of MTHFR1298AC TS5-UTR 3R2R and MTRR66AG may be biomarkers for patients receiving 5-FU regimens.